The Impact of Racial Bias in Patient Care and Medical Education: Let's Focus on the Educator - Leonor Corsino; Kenyon Railey; Katherine Brooks; Daniel Ostrovsky; Sandro O. Pinheiro; Alyson McGhan-Johnson; Blanca Iris Padilla (Association of American Medical Colleges, 2021)
Introduction Racial bias in health care is well documented. Research shows the presence of racial bias among health care providers. There is a paucity of workshops focused on racial bias effects in health professions educators. Method Two to three workshops were delivered to a diverse group of clinical educators from three programs at a major academic institution. Each workshop included a brief multimedia presentation followed by a facilitated group discussion. Participants completed the online Implicit Association Test (IAT), a baseline demographic questionnaire, and a brief post-then-pre questionnaire. Results Twenty-four faculty participated in the study (six physicians, eight nurse practitioners, 10 physician assistants). Nineteen (90%) were women, 18 (86%) were White, nine (43%) had more than 10 years of experience as educators, and seven (35%) had previously participated in a biases program. Seventeen completed the IAT. Sixteen educators agreed or strongly agreed that bias has a significant impact on patients' outcomes at the end of the workshop compared to 17 before the workshop. Seventeen educators agreed or strongly agreed that recognizing their own racial bias would positively alter their teaching practice after the workshop compared to 15 before the workshop. Discussion This series of workshops was created to fill a gap regarding the impact of racial bias on patient outcomes, health disparities, and health professions education. The impact of racial bias in health professions education and the long-term impact of awareness and knowledge of racial bias in education are areas needing further evaluation.